Archaeologies of Remembrance
XIV, 310 p.
Keywords: How did past communities and individuals remember through social and ritual practices? How important were mortuary practices in processes of remembering and forgetting the past? This innovative new research work focuses upon identifying strategies of remembrance. Evidence can be found in a range of archaeological remains including the adornment and alteration of the body in life and death, the production, exchange, consumption and destruction of material culture, the construction, use and reuse of monuments, and the social ordering of architectural space and the landscape. This book shows how in the past, as today, shared memories are important and defining aspects of social and ritual traditions, and the practical actions of dealing with and disposing of the dead can form a central focus for the definition of social memory.